Electrochemical grafting of 4‐phenoxybenzoic acid units onto oxidized carbon fibers as a first step for high temperature composites. Issue 3 (26th April 2013) - Soulis, Spyridon; Triantou, Despina; Simitzis, Johannis
ABSTRACT The electropolymerization of 4‐phenoxybenzoic acid (4‐PBA) onto carbon fibers (CFs) was studied as a way to synthesize coated CFs with grafted poly(para‐phenyl ether ketone) (p‐PEK) and enhance their wettability by matrices such as PEK or PEEK. Since the pristine CFs were not electrochemically active enough, a proper electrochemical oxidation treatment using sulfuric acid was applied, capable of creating oxygen‐containing groups onto their surface. The groups formed in the oxidized CFs were electron acceptors and their amount was quasi‐quantitatively evaluated based on their ability to absorb dye from aqueous solutions. The graft electropolymerization of 4‐PBA onto the CFs electrode was achieved at anodic potentials using cyclic voltammetry (CV). The grafted coating had a thickness of up to 0.35 μm. The materials were characterized using FTIR, NMR, SEM, and TGA. A possible reaction mechanism is proposed, for the grafting of 4‐PBA units onto the carboxyl groups of the treated CFs. The coated CFs were more thermally stable compared to the treated CFs without grafting. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1466–1478, 2013